2015
DOI: 10.1007/s12192-014-0542-3
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone protects human peripheral blood lymphocytes from γ-irradiation-induced apoptosis and DNA damage

Abstract: Radiation-induced cellular injury is attributed primarily to the harmful effects of free radicals, which play a key role in irradiation-induced apoptosis. In this study, we investigated the radioprotective efficacy of edaravone, a licensed clinical drug and a powerful free radical scavenger that has been tested against γ-irradiation-induced cellular damage in cultured human peripheral blood lymphocytes in studies of various diseases. Edaravone was pre-incubated with lymphocytes for 2 h prior to γ-irradiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…It has a complex polyphenolic hydroxyl structure and is soluble in water and some organic solutions. Tannin has proven useful for the prevention and treatment of ionizing radiation pollution [6,7]. Sunan et al reported that tannin effectively improved the survival of human megakaryocytes exposed to 10 Gy of 60Co γ-rays by decreasing the production of reactive oxygen species (ROS) and suppressing apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has a complex polyphenolic hydroxyl structure and is soluble in water and some organic solutions. Tannin has proven useful for the prevention and treatment of ionizing radiation pollution [6,7]. Sunan et al reported that tannin effectively improved the survival of human megakaryocytes exposed to 10 Gy of 60Co γ-rays by decreasing the production of reactive oxygen species (ROS) and suppressing apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other study has shown that compared to the placebo group, an increase in T cell proliferation was seen in the vitamin C-supplemented group [37]. Similar results were obtained by Chen et al (2015) who found edaravone enhanced cell survival at concentrations ranging from 10 to 100 µM in a dose-dependent manner at 24 h post-irradiation [38].…”
Section: Discussionsupporting
confidence: 77%
“…Ionizing radiation induces DNA damages via direct deposition of energy to DNA and indirect interactions with water within the cells that result in the formation of free radicals. 16 Although living cells to protect themselves from reactive oxygen species (ROS) are well equipped with endogenous cellular and enzymatic compounds such as superoxide dismutase, glutathione (GSH) peroxidase, and catalase and nonenzymatic compounds such as vitamin C, uric acid, and GSH, 17 when the generation of ROS increases, the endogenous cellular compounds are not able to remove them, thus ROS scavenger ability is critical for the development of radioprotective agents. 18 Various compounds with radioprotective potential have been the subject of recent studies.…”
Section: Discussionmentioning
confidence: 99%